They Are Human Beings Too Attitudes Towards LGBT Among Present Day Malaysians: The Human Dignity Factor - Jerome, Collin; Ting, Su Hie; Jacinta Jiin-Yih, Yeo (2021)
Recent years have witnessed a proliferation of research on lesbian, gay, bisexual, and transgender (LGBT) individuals in Malaysia, which pay attention to the various aspects of their lives and livelihoods. Although several studies have examined the attitudes of the Malaysian public towards LGBT, these studies have identified religion and gender role beliefs as the key factors that influenced those attitudes. The present study extended this line of research by examining the human dignity factor that shaped Malaysians‟ attitudes towards LGBT. Data were gathered through in-depth interviews with 14 participants and based on a series of questions relating to their attitudes and opinions of LGBTs. The analysis of the data revealed three dominant themes: (1) LGBTs were accepted on the basis that they were human beings, (2) LGBTs should be respected for what they were, what they believed in, and how they lived their lives, and (3) LGBTs should be treated equally and not be discriminated against. The findings of the present study suggest the need to consider human dignity as one of the key factors that may have contributed to the steadily increasing trend towards public acceptance of LGBTs in present-day Malaysia.